1990
DOI: 10.1007/bf01646861
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of vitamin B6 and fixed combinations of vitamin B1, B6, B12 on nociceptive activity evoked in the rat thalamus: Dose-response relationship and combinations with morphine and paracetamol

Abstract: Nociceptive activity was elicited in neurones of the thalamus by supramaximal electrical stimulation of afferent C fibres in the sural nerve of rats under urethane anesthesia. The fixed combination of vitamin B1, B6, and B12 (Neurobion) as well as of vitamin B6 administered by i.p. injection dose-dependently reduced the evoked nociceptive activity. The ED50 of Neurobion is 4.6 ml/kg (at 100 min after injection) and that of vitamin B6 is 189 mg/kg (at 90 min after injection). The minimum effective doses of Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
9

Year Published

1992
1992
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 12 publications
0
10
0
9
Order By: Relevance
“…However, other investigators [Eschalier et al, 1983;Bromm, 1995;Reyes-García et al, 1999] have reported that B vitamins, alone or combined, are devoid of antinociceptive action in several models of pain. Jurna et al [1990] proposed that this controversy could be due to the use of different pain stimuli.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, other investigators [Eschalier et al, 1983;Bromm, 1995;Reyes-García et al, 1999] have reported that B vitamins, alone or combined, are devoid of antinociceptive action in several models of pain. Jurna et al [1990] proposed that this controversy could be due to the use of different pain stimuli.…”
Section: Discussionmentioning
confidence: 98%
“…An antiinflammatory effect has also been reported in the carrageenin-induced edema test [Bartoszyk and Wild, 1989;Hanck and Weiser, 1985]. Moreover, the individual administration of thiamine and pyridoxine produced antinociception in acetic acid-induced pain or pain induced by supramaximal electrical stimulation of afferent C fibers [Jurna et al, 1990;Franc -a et al, 2001]. In contrast, negative results have also been observed.…”
Section: Introductionmentioning
confidence: 83%
“…Second, several studies have indicated that pyridoxine alone and the mixture of B vitamins increase synthesis and secretion of serotonin and ␥ -aminobutyric acid [35][36][37] in several brain areas. In addition, the antinociceptive effect of B vitamins has been associated with an increase of afferent inhibitory control of nociceptive neurons at the spinal cord [38] and a reduction of the response of thalamic neurons to nociceptive stimulation [39] . Third, B vitamins may contribute to the recovery of nerve function in conditions of nerve injury [27,40,41] .…”
Section: Antiallodynic Effect Of B Vitamins and Dexamethasonementioning
confidence: 99%
“…Recently, the analgesic and anti-inflammatory effects of several members of the Vitamin B complex such as B 1 6 [8][9][10][11][12][13][14] , inflammatory 10,[12][13][15][16][17][18] , neuropahtic pain [19][20] and also inflammation 11,18 after single or repeated administrations. On the other hand, single dose or short term (7days) supplementation of vitamin B 12 alone failed decrease pain in in rodents [10][11] .…”
Section: Introductionmentioning
confidence: 99%